Pengaruh Lingkungan Kerja, Pengembangan Karir dan Promosi Jabatan Terhadap Kepuasan Kerja Karyawan: Studi Kasus: PT. PP. London Sumatra Indonesia Tbk - Elvi Denovpriani; Muhammad Wadud (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze and prove the influence of the work environment, career development, and job promotion on the job satisfaction of employees at PT. PP. London Indonesia Tbk, Muratara Regency. The research method used is descriptive quantitative, with the population being all employees at PT. PP. London Indonesia Tbk, Muratara Regency, totaling 113 people. The sample in this study uses a saturated sampling method, which includes the entire population in the research. Data collection methods include questionnaires, interviews, and observations. Data analysis in this research uses multiple linear regression, hypothesis testing using t-tests, and coefficient of determination. The results of the multiple linear regression test are KK = 2.256+0.427LK+0.079PK+0.634PJ. The ttest results show that the work environment, career development, and job promotion have an effect on the job satisfaction of employees at PT. PP. London Indonesia Tbk, Muratara Regency. The coefficient of determination is 89.2%, while the remaining percentage is influenced by other variables not examined in this study.